Channel width selection scheme for better utilisation of WLAN bandwidth. Issue 5 (1st February 2014) - Stelter, A.
Abstract : The channel access method, defined in the IEEE 802.11ac draft, forces stations (STAs) to transmit data over the widest currently available channel supported by the basic service set (BSS). Unfortunately, the transmission in a wide channel is very inefficient if data frames are short. A channel width selection scheme (CWSS) is proposed which reduces the bandwidth used by the STA, if the transmitted data frame is not sufficiently long. Simulation results show that the CWSS allows a better bandwidth utilisation in an environment of overlapping 802.11ac BSSs. The CWSS is compatible with the channel access procedure defined in the IEEE 802.11ac.